The effectiveness of visual media in literature-based classroom / Nor Azyyati Md Saad, Diane Sima Anak Douglas Telajan and Norazrin Zamri - Md Saad, Nor Azyyati; Douglas Telajan, Diane Sima; Zamri, Norazrin (Universiti Teknologi MARA, Kedah, 2014)
A typical Literature-based classroom consists of the students, the teacher and the Literature texts. This has resulted in the loss of students’ interest towards learning Literature. Apart from literary texts such as novels, poems and short stories, most other materials, in essence, lack the power of capturing students’ interest towards understanding the literary meanings of Literature texts. Another setback to this is the teacher’s dependency on the textbook which results in a monotonous lesson as the teacher is not using creative methods to engage students in a Literature lesson. This research aims to investigate the effectiveness of implementing visual media in the teaching of Literature towards students’ interest and understanding of Literature texts. Based on the findings, the research has revealed that there is a significant correlation between the independent variable; visual media in Literature-based classroom, and the dependent variables; students’ interest and understanding of Literature texts. The majority of the respondents agreed that visual media in Literature-based classroom enabled them to understand their Literature texts better. Moreover, the use of visual media in Literature-based classroom can be one of the creative ways to attract their interest.